2017
DOI: 10.22159/ajpcr.2017.v10s1.19566
|View full text |Cite
|
Sign up to set email alerts
|

Field Programmable Gate Array Implementation of a Variable Leaky Least Mean Square Adaptive Algorithm

Abstract: Adaptive noise cancellation is an extensively researched area of signal processing. Many algorithms had been studied such as least mean square algorithm (LMS), recursive least square algorithm, and normalized LMS algorithm. The statistical characteristics of noise are fast in nature and the algorithms for noise cancellation should converge fast. Since LMS algorithm has slow convergence; in this paper, a variable leaky LMS (VLLMS) algorithm is explored. VLLMS is implemented using the concept of hardware-softwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…In [19], a variable leaky LMS algorithm based on the greedy heuristic algorithm has been leveraged to enhance with the high eigenvalue input. In [20], the authors have implemented the variable leaky LMS in the field programmable gate array implementation. The results have been shown that the algorithm can explore the various digital filter architecture.…”
Section: Introductionmentioning
confidence: 99%
“…In [19], a variable leaky LMS algorithm based on the greedy heuristic algorithm has been leveraged to enhance with the high eigenvalue input. In [20], the authors have implemented the variable leaky LMS in the field programmable gate array implementation. The results have been shown that the algorithm can explore the various digital filter architecture.…”
Section: Introductionmentioning
confidence: 99%